Effectiveness of BSF Frass, Bioslurry, and Organic Compost at Different Application Rates on the Growth and Biomass of Water Spinach (Ipomoea reptans Poir) - Sri Wahyuni; Muhammad Taufik Awaludin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Organic waste can be processed into environmentally friendly fertilisers that support plant growth and reduce environmental pollution. This study evaluated the effects of black soldier fly frass, bioslurry, and organic compost at different application rates on the growth and biomass of water spinach (Ipomoea reptans Poir.). The experiment was conducted from November 2025 to March 2026 at PT Swen Inovasi Transfer, Bogor, Indonesia, using a completely randomised design. Treatments consisted of three organic fertiliser types applied at 0, 100, 200, and 300 g per polybag. Plant height, leaf length, number of leaves, and fresh weight were observed. Data were analysed using analysis of variance followed by Duncan’s Multiple Range Test at the 5% significance level. Fertiliser type, application rate, and their interaction did not significantly affect plant height, leaf length, or number of leaves, but significantly influenced fresh weight. The highest fresh weight of 8.40 g was obtained with 200 g frass and 200 g bioslurry treatments. These results indicate that frass and bioslurry at 200 g per polybag are promising for increasing water spinach fresh biomass.